OPTIMUM VECTOR SCALARIZATION CONTROL CRITERIA IN CONFLICTING SYSTEMS - Ignatov, V. A.; Guziy , N. N. (Problems of Informatization and Management, 2021)
The issues of optimal control of scalarization of vector criteria in conflicting systems are considered, the conditions for the minimax and optimal behavior of the defending side are determined.